Analisis Studi Pendahuluan Lembar Kerja Siswa Berbasis Model Inquiry Based Learning Pada Pembelajaran Fisika Abad 21 - Samudra, Elmi Yanto Adhar; Yulkifli, Yulkifli (Universitas Negeri Padang, 2019)
21st century physics learning makes students think critically, creatively and innovatively in mastering science concepts. The use of teaching materials and the selection of the right model determine success to achieve the expected goals in the physics learning process. The student worksheet based on inquiry based learning models can increase the activeness and independence of learning of students in investigating, discovering concepts, and being able to implement learning materials with their lives. This study aims to analyze a preliminary study of student worksheets based on inquiry based learning models in physics learning. This research is a descriptive study conducted through observation in high schools (SMAN 4 Padang) with the research sample being students of class X MIPA. Preliminary study analysis of student worksheets based on inquiry based learning models includes analysis of graduate competency standards, student analysis, analysis of learning activities, and assessment analysis. The instrument used in the study was in the form of questionnaires and interview sheets. The results showed that the analysis of graduate competency standards obtained an average value of 73.33, analysis of learners obtained an average value of 67.75, an analysis of learning activities obtained an average value of 70.63 and assessment analysis obtained an average value of 84.23. so, it is necessary to develop student worksheets based on inquiry based learning models